Pengaruh Layanan COD dan Gratis Ongkir Terhadap Minat Beli Konsumen Pada e-commerce Shopee - Khairul Marlin; R Dilla Juniati; Khairulis Shobirin (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
The purpose of this study is to find out how much impact COD services and free of charge are on student purchasing interest in Shopee e-commerce. The type of research is field research with a quantitative approach. Data Collection Technique using questionnaires. The population in this study is students of Sharia Business Management Study Program Faculty of Islamic Economics and Business UIN Mahmud Yunus Batusangkar force 2019, 2020, 2021 and 2022 who use and shop at e-commerce Shopee with criteria have made a minimum purchase of five times and a minimum of spending Rp.200,000. The sample in the study was determined by the Slovin formula, which is 145 respondents. Data processing is done with the help of SPSS applications. The results of the study showed that partially the variable COD (X1) service had a significant effect on the interest of buying (Y) students in e-commerce Shopee in Sharia Business Management Study Program students FEBI UIN Mahmud Yunus Batusangkar, the free variable of the disk (X2) also had a significant effect on the interest of buying (Y) student of Shopee e-commerce at students of Sharia Business Management Study Program FEBI UIN Mahmud Yunus Batusangkar. Simultaneously, COD (X1) and free (X2) services together affect the variable interest of purchasing (Y) students in e-commerce Shopee on study in Sharia Business Management Study Program FEBI UIN Mahmud Yunus Batusangkar